2011
DOI: 10.1007/s12185-011-0974-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII (rFVIIa/NovoSeven®) in the management of severe postpartum haemorrhage: initial report of a multicentre case series in Japan

Abstract: Only a limited number of case reports documenting the off-label use of recombinant factor VIIa (rFVIIa) in Japanese patients with postpartum haemorrhage (PPH) have been published. Data on Japanese cases with severe PPH in which rFVIIa was administered were collected. Data of obstetric haemorrhage patients treated with rFVIIa between 2005 and 2010 were retrospectively collected throughout Japan. The data included patients' background information, blood product requirements, dose/timing of rFVIIa, and adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…The off‐label use of rFVIIa, which was originally developed for the treatment of hemophilia, has been reported for the management of PPH . Existing data are retrospective but cessation of bleeding is reported in some women with major hemorrhage . The Australian and New Zealand Haemostasis Registry reported improvement (cessation or significant slowing) in bleeding in 76% of women (n = 71/94) who were administered rFVIIa (median dose, 92 μg/kg) for the treatment of acute PPH and a Northern European registry reported improvements in 80% of women with major PPH (n = 92).…”
Section: Administration Of Hemostatic Agents and Blood Productsmentioning
confidence: 99%
“…The off‐label use of rFVIIa, which was originally developed for the treatment of hemophilia, has been reported for the management of PPH . Existing data are retrospective but cessation of bleeding is reported in some women with major hemorrhage . The Australian and New Zealand Haemostasis Registry reported improvement (cessation or significant slowing) in bleeding in 76% of women (n = 71/94) who were administered rFVIIa (median dose, 92 μg/kg) for the treatment of acute PPH and a Northern European registry reported improvements in 80% of women with major PPH (n = 92).…”
Section: Administration Of Hemostatic Agents and Blood Productsmentioning
confidence: 99%
“…In postpartum hemorrhage, common non-operative management involves the use of uterine stimulants, bimanual compression of the uterus and uterine artery embolization [12]. More recently, rFVIIa has also been used to prevent or control bleeding in postpartum hemorrhage [13]. However, it has thrombotic risks, and there are no definitive target FVII levels or optimal treatment regimens to maintain hemostasis [14].…”
Section: Discussionmentioning
confidence: 99%
“…After the formal beginning of this randomized controlled trial (RCT), Welsh et al and Phillips et al published, based on their experience and on the published cases series, guidelines and an algorithm for the use of rhuFVIIa at 90 lg kg À1 in patients with PPH after surgical intervention (arterial embolization, arterial ligatures and peripartum hysterectomy) [18,19]. A recent systematic review of 272 patients suggested that rhuFVIIa might be useful for the management of severe refractory PPH compared with standard treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%